DIFFERENTIAL EFFECTS OF PEROXISOME PROLIFERATOR-ACTIVATOR RECEPTOR (PPAR) ALPHA AND GAMMA AGONISTS ON BODY WEIGHT AND ADIPOSE DEPOTS IN FRUCTOSE FED WISTAR RATS - Atanasovska, Emilija; Pavlovska, Kristina; Jakjovski, Krume; Gjorgjievska, Kalina; Zendelovska, Dragica; Petrushevska, Marija; Ahmeti, Irfan; Zafirov, Dimce; Labacevski, Nikola (Journal of Morphological Sciences, 2018)
Aims: To investigate the effect of fenofibrate (PPAR-alpha agonist) and rosiglitazone (PPAR-gamma agonist) on body weight and adipose depots in an experimental model of the metabolic syndrome. Methods: Metabolic syndrome was induced in 48 male Wistar rats by adding a fructose in drinking water (10% solution) for 12 weeks. During the last 4 weeks, 16 rats were treated with fenofibrate (100 mg/kg/day), 16 rats were treated with rosiglitazone (5 mg/kg/day) by intragastric tube, while the remaining 16 did not receive any medication (fructose group). Another control group of 16 rats consumed standard rat chow and water for 12 weeks. Results: Chronic fructose administration for 12 weeks significantly increased the body weight (p<0.05), as well as the weight of the measured fat pads: perirenal (p<0.001) and epididymal (p<0.001) as representatives of the visceral adipose depots and the inguinal pads (p<0.05) as a representative of the subcutaneous adipose depots compared to the control group. This was accompanied with a decrease of the subcutaneous/visceral fat ratio. Treatment with fenofibrate over the final 4 weeks significantly decreased the body weight (p<0.001) and the weight of the epididymal, perirenal and inguinal fat pads (p<0.001 for all parameters), without changes of the subcutaneous/visceral fat ratio. On the other hand, rosiglitazone promoted weight gain. Treatment with this PPAR-gamma agonist significantly decreased the weight of the epididymal (p<0.01) and perirenal (p<0.05) pads, but increased the weight of the inguinal fat pads (p<0.001) compared to the fructose group, which led to an increase of the subcutaneous/visceral fat ratio. Conclusion: This study indicates that treatment with the PPAR-alpha agonist fenofibrate decreases body weight and reduces the fat depots, whereas PPAR-gamma agonist promotes weight gain and a body fat redistribution from visceral towards subcutaneous depots in an animal nutritive model of the metabolic syndrome.   Key words: fructose, fenofibrate, rosiglitazone, PPAR, metabolic syndrome, body weight